Answer:
![x_(1)=(-13+√(153))/(2)\\x_(2)=(-13-√(153))/(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/ysf9t54v7hyig6zv0jqpe4gbhdr4sltzxu.png)
Explanation:
The given expression is
![x^(2)=-13x-4](https://img.qammunity.org/2020/formulas/mathematics/high-school/60a4yi8zu0aj5dkon96ry4ty3dgyexgck5.png)
To solve this quadratic equation, we first need to place all terms in one side of the equation sign
![x^(2) +13x+4=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/glxjumflgijfg36pbj30zniz47auxuzckt.png)
Now, to find all solutions of this expression, we have to use the quadratic formula
![x_(1,2)=\frac{-b\±\sqrt{b^(2)-4ac}}{2a}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5f6thejtbe2lhy43v9abiiwfpp8baz3mhj.png)
Where
,
and
![c=4](https://img.qammunity.org/2020/formulas/mathematics/high-school/6puv6y6l8f7q46jgzoz3hy98ed0l4pd0wm.png)
Replacing these values in the formula, we have
![x_(1,2)=\frac{-13\±\sqrt{(13)^(2)-4(1)(4)}}{2(1)}\\x_(1,2)=(-13\±√(169-16))/(2)=(-13\±√(153))/(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/9o861kagul6wmh1ihwbz9ca8nt0dgmehfr.png)
So, the solutions are
![x_(1)=(-13+√(153))/(2)\\x_(2)=(-13-√(153))/(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/ysf9t54v7hyig6zv0jqpe4gbhdr4sltzxu.png)
If we approximate each solution, it would be
![x_(1)=(-13+√(153))/(2)\approx -0.32\\\\x_(2)=(-13-√(153))/(2) \approx -12.68](https://img.qammunity.org/2020/formulas/mathematics/high-school/idy2yruosw3yp0dbeo6f3hkbgaryu9env8.png)